Evaluating effects of bycatch and fisheries-induced evolution on oceanic trophic systems - Nihlani, Dr. Ankita; John, Dr. Byju; Benerjee, Sayanti (International Journal of Aquatic Research and Environmental Studies, 2025)
Human activities, particularly fishing, have been recognized as a primary contributor to the decline in biodiversity in the open ocean. This article examines the diversity trends and ecological characteristics of bycatch populations in Fish Aggregating Devices (FADs) and Free School settings within the tropical tuna purse-seine fisheries in the eastern Atlantic Seaboard. Information was gathered from scientific observer programs conducted from 2000 to 2025 aboard Spanish and French ships. Based on the fishing method, the findings indicated varying structural and diversity trends in bycatch assemblies, revealing more species and variety in FAD sets compared to Free School settings. Bycatch populations showed preferences for particular oceanographic features of the Atlantic Seaboard, including the tropical and annual coastal rising structures, the Cape Lopez front structure, and the Guinea domes. The kind of habitat and surface water temperature significantly influence the diversity trends of these organisms. These findings validate the necessity of incorporating several methodologies to investigate the marine environment for the practical application of the Ecosystem Approaches to Fishery Management (EAFM).
Keywords: Bycatch, Fisheries, Oceanic trophic systems, Ocean